1997
DOI: 10.1046/j.1365-2265.1997.3231152.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of intravenous amiodarone on sulphate metabolites of thyroid hormones in arrhythmic patients

Abstract: Our data indicate that a loading dose of intravenous amiodarone in patients with cardiac dysrhythmias is followed by a very rapid and progressive increase in circulating T3-S levels, possibly due to an inhibition of type 1-iodothyronine de-iodinase. Since T2-S and T1-S, common final metabolites of the thyroid hormone sulphation pathways remained unchanged, our data suggest that the total amount of thyroid hormone degraded by sulphation pathways remains unaltered during amiodarone treatment. Finally our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Moreover, individuals with thicker epicardial adipose tissue (EAT) have exhibited an inferior response to antiarrhythmic therapy (Ahmet et al, 2015). The research revealed that EAT thickness and left atrial volume index (LAVI) were independent predictors of prolonged atrial electromechanical delay (AEMD), and both were closely associated (Iervasi et al, 1998). This may account for the poorer response to antiarrhythmic therapy seen in patients with thicker EAT.…”
Section: Meta-analyses and Systematic Reviews On La-eat Thickness And...mentioning
confidence: 99%
“…Moreover, individuals with thicker epicardial adipose tissue (EAT) have exhibited an inferior response to antiarrhythmic therapy (Ahmet et al, 2015). The research revealed that EAT thickness and left atrial volume index (LAVI) were independent predictors of prolonged atrial electromechanical delay (AEMD), and both were closely associated (Iervasi et al, 1998). This may account for the poorer response to antiarrhythmic therapy seen in patients with thicker EAT.…”
Section: Meta-analyses and Systematic Reviews On La-eat Thickness And...mentioning
confidence: 99%
“…Moreover, individuals with thicker epicardial adipose tissue (EAT) have exhibited an inferior response to antiarrhythmic therapy (57). The research revealed that EAT thickness and left atrial volume index (LAVI) were independent predictors of prolonged atrial electromechanical delay (AEMD), and both were closely associated (58). This may account for the poorer response to antiarrhythmic therapy seen in patients with thicker EAT.…”
Section: Impact Of La-eat Thickness On Af Outcomes and Recurrencementioning
confidence: 99%